Analisis Pemanfaatan Dana Desa dalam Program Ketahanan Pangan Berbasis Partisipasi Pemberdayaan Masyarakat (Studi di Kecamatan Banama Tingang Kabupaten Pulang Pisau Kalimantan Tengah) - Lindayadia, Lindayadia; Hayati, Mulida; Fransisco, Fransisco (Dinasti Research, 2025)
Implementation of village fund utilization in a community empowerment-based food security program in Banama Tingang District, Pulang Pisau Regency, as well as the obstacles encountered in the implementation process. This research employs an Empirical Juridical Method, which is an approach based on primary legal materials by examining theories, concepts, legal principles, and legislation related to the topic. The implementation of the village food security program is crucial for improving community welfare. Therefore, proper management by the village government is necessary to achieve the objectives and targets of village fund allocation, particularly those related to community empowerment activities. The community must share a common vision and mission to ensure that development reaches its intended goals. Efforts to empower rural communities are essential to enhance their capabilities by encouraging, motivating, and developing the potential of local resources. This is crucial to the success of central government programs, including the food security program.